Reference Equation for Prediction of a Total Distance During Six-minute Walk Test using Indonesian Anthropometrics - Nury Nusdwinuringtyas; Widjajalaksmi Widjajalaksmi; Faisal Yunus; Idrus Alwi (Acta Medica Indonesiana)
Aim: to develop a reference equation for prediction of the total distance walk using Indonesian anthropometrics of sedentary healthy subjects. Subsequently, the prediction obtained was compared to those calculated by the Caucasian-based Enright prediction equation. Methods: the cross-sectional study was conducted among 123 healthy Indonesian adults with sedentary life style (58 male and 65 female subjects in an age range between 18 and 50 years). Heart rate was recorded using Polar with expectation in the sub-maximal zone (120-170 beats per minute). The subjects performed two six-minute walk tests, the first one on a 15-meter track according to the protocol developed by the investigator. The second walk was carried out on Biodex®gait trainer as gold standard. Results: an average total distance of 547±54.24 m was found, not significantly different from the gold standard of 544.72±54.11 m (p>0.05). Multiple regression analysis was performed to develop the new equation. Conclusion: the reference equation for prediction of the total distance using Indonesian anthropometrics is more applicable in Indonesia.